L'Oeuvre Post-Retour D'Exil de Mongo Beti - Mokam, Yvonne-Marie (The University of Arizona., 2009)
The Return Home : Mongo Beti's Late OeuvreIn 1991 amid the wave of democracy sweeping Africa, Mongo Beti returned to his native country of Cameroon to continue his literary career after 32 years of exile in France. My dissertation investigates the originality of his homecoming discourse. I explore how this prominent writer's late oeuvre illustrates his struggle to re-discover the country he left decades earlier as well as how his experience of returning shaped a new literary perception. His work after returning home reflects his gradual re-acquaintance with and re-integration into his native country. I argue that at the outset, his perception is initially guided by a backward glance on the past and that his assessment of the present aims at resisting pessimistic representations of Africa. In his later works, however, one cannot but notice the same sentiments of dissatisfaction and disillusion that were based on his first hand experience. To this extent, Mongo Beti's post-return literature can be considered dynamic as it evolved over time. A diachronic approach allowed me to examine his changing perceptions and representations of Africa based on the magnitude of his comprehension of his environment at each point in time. His post-return writing demonstrates a progressive redefinition of some of his previous narrative techniques as regards such elements as political resistance, authoritative narrators, linear unfolding of the plot, time and space, and character development. My analysis also questions the concept of "home" as a place of safety and refuge just as his post-return novels portray exile as an ambiguous state of being in-between worlds, as an expression of a simultaneous connection to the "new old" home and the distant former one abroad. Therefore, there is a shift in Mongo Beti's post-return discourse away from questions of national responsibility and social progress rooted in a consciousness of belonging to a defined community. The conceptual organization of my dissertation is derived from my reading of each of the four texts of the post-return era, and the way they illustrate the author's process of re-discovery of postcolonial Cameroon.